Progress and Prospect of Solid Waste Utilization in Construction Industry: A Bibliometric Analysis Based on CiteSpace and VOSviewer - Runrun Dong; Huixian Yu; Jing Lu (Buildings)
The high-value-added and resourceful reuse of solid waste is regarded as a promising technological approach within the construction industry, playing a vital role in advancing sustainable development and ecological civilization. In this study, VOSviewer and CiteSpace were utilized to systematically perform a bibliometric analysis of research related to the reutilization of solid waste in the construction sector, using data from the Web of Science Core Collection and Scopus databases. The analysis focused on publication volume over the last decade, global collaboration networks, thematic journals, keyword co-occurrence, and timeline clustering. The results reveal that: (1) The number of publications related to solid waste in construction has steadily increased over the last decade; (2) Significant research contributions have been observed from China. However, a cohesive core of contributing authors has yet to emerge, and broader, more equitable international collaboration remains necessary; (3) Research foundations span disciplines such as environmental science, materials science, physics, and chemistry, indicating a clear trend of interdisciplinary integration; (4) Current research primarily explores the performance and environmental impacts of concrete and waste-derived materials. Over time, topics have expanded from early explorations to include environmental assessments, waste management, and the circular economy, increasingly advanced technologies to investigate high-performance and diverse material applications. In the future, the energy efficiency and green sustainability of solid waste are expected to draw continued attention, with emerging technologies such as 3D printing and artificial intelligence likely to foster more interdisciplinary research in optimizing material performance.